Primary care for individuals with serious mental illness (PriSMI): protocol for a convergent mixed methods study. Issue 9 (20th September 2022) - Grudniewicz, Agnes; Peckham, Allie; Rudoler, David; Lavergne, M Ruth; Ashcroft, Rachelle; Corace, Kimberly; Kaluzienski, Mark; Kaoser, Ridhwana; Langford, Lucie; McCracken, Rita; Norris, W Craig; O'Riordan, Anne; et al.
Abstract : Introduction: People with serious mental illness (SMI) have poor health outcomes, in part because of inequitable access to quality health services. Primary care is well suited to coordinate and manage care for this population; however, providers may feel ill-equipped to do so and patients may not have the support and resources required to coordinate their care. We lack a strong understanding of prevention and management of chronic disease in primary care among people with SMI as well as the context-specific barriers that exist at the patient, provider and system levels. This mixed methods study will answer three research questions: (1) How do primary care services received by people living with SMI differ from those received by the general population? (2) What are the experiences of people with SMI in accessing and receiving chronic disease prevention and management in primary care? (3) What are the experiences of primary care providers in caring for individuals with SMI? Methods and analysis: We will conduct a concurrent mixed methods study in Ontario and British Columbia, Canada, including quantitative analyses of linked administrative data and in-depth qualitative interviews with people living with SMI and primary care providers. By comparing across two provinces, each with varying degrees of mental health service investment and different primary care models, results will shed light on individual and system-level factors that facilitate or impede quality preventive and chronic disease care for people with SMI in the primary care setting. Ethics and dissemination: This study was approved by the University of Ottawa Research Ethics Board and partner institutions. An integrated knowledge translation approach brings together researchers, providers, policymakers, decision-makers, patient and caregiver partners and knowledge users. Working with this team, we will develop policy-relevant recommendations for improvements to primary care systems that will better support providers and reduce health inequities.